Familial hypercholesterolemia with early coronary atherosclerotic heart disease: A case report - Luo, Yanhong (Exp Ther Med, 2019)
Patients with familial hypercholesterolemia usually present with high levels of serum low-density lipoprotein, xanthomas and early coronary artery disease. A 13 years old female patient was admitted to Children's Hospital of Chongqing Medical University presenting symptoms of heart failure. Laboratory tests showed that her cholesterol and low-density lipid levels were extremely high. Electrocardiogram test revealed that she had sinus tachycardia, QT lengthening and ST-T change. Multiple cardiac function abnormalities were diagnosed by echocardiogram. Multiple coronary artery stenosis was determined by computed tomography angiography. After the combination of lipid lowering, anti-thrombosis, and cardiac remodeling therapies, the patient's symptoms were significantly improved and the patient was discharged.